Effects of resisted sprints with changes of direction through several relative loads on physical performance in soccer players - Rodriguez-Osorio, D.; Gonzalo-Skok, O.; Pareja-Blanco, F. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To compare the effects of resisted change-of-direction (COD) movements, using several relative loads, on soccer players` physical performance. Methods: Fifty-four male soccer players were randomly assigned to 1 of the following 3 groups, which differed only in the magnitude of the external load used during the COD training: COD training without external load (COD-0; n=16), COD training with a 12.5% body-mass external load (COD-12.5; n=19), and COD training with a 50% body-mass external load (COD-50; n=19). Participants performed the specific COD training twice per week for 6 wk. Before and after the training period, a battery of tests was completed: countermovement jump, 30-m running sprint (time in 10 m [T10], 20 m [T20], and 30 m [T30]), L-run test, and V-cut test. Results: Within-group comparisons showed substantial improvements in countermovement jump and T10 (likely) in COD-0, whereas countermovement jump, T10, and T20 were substantially enhanced (possibly to likely) in COD-50. COD-12.5 induced substantial improvements in all analyzed variables (likely to most likely). Between-groups comparisons showed better effects on all analyzed variables for COD-12.5 than for COD-0 (possibly to very likely), whereas COD-50 only showed possibly better effects than COD-0 on T10. In addition, COD-12.5 induced a better effect on L-run and V-cut tests than COD-50 (possibly to likely). Conclusions: These results indicate that COD training, especially moderate load (12.5% body mass) resisted COD training, may have a positive effect on COD skills, running sprint performance, and jumping ability in young soccer players.